“En commençant par Moïse et les prophètes …”: Études vétérotestamentaires. By Guy Couturier - Williamson, H. G. M. (The journal of theological studies, 2009)
A Pupil of W. F. Albright at Johns Hopkins University and of R. de Vaux at the École biblique in Jerusalem, Guy Couturier taught for most of the remainder of his career in Montreal. His work was mainly published in French in Canadian journals such as Église et théologie and Sciences religieuses, which are not widely read internationally, and also in a number of volumes of collected essays also largely ignored outside French-speaking circles. It is thus very welcome that 23 of his main articles have here been collected and republished in a uniform and attractive format., The collection is varied in every sense. In length, they span a few pages to one or two that are over 50 pages long.